Digital Transformation in Art Pedagogy: Hybrid Learning Modalities for Skill Transfer - Flowers, Lawrence (Journal of Research in Vocational Education, 2025)
Digital technology has transformed traditional art education, reshaping creativity, skill acquisition, and teaching methods. This study examines its effects through qualitative and quantitative data from students, educators, and institutions, highlighting enhanced accessibility and creative opportunities alongside challenges like reduced hands-on expertise and over-reliance on digital tools. It explores how instructors adapt to integrate both approaches and assesses impacts on artistic expression and cognition. Advocating a balanced curriculum, the research underscores the need to preserve tactile learning while leveraging digital advancements, ensuring students gain versatile skills for contemporary art practice. The results show that digital technologies improve accessibility to a variety of artistic styles, open up new creative possibilities, and promote online platform collaboration. But they also present problems, as less practical expertise with tangible materials, an excessive dependence on digital techniques, and the possible undervaluation of conventional artistic abilities. The study also looks into how technology changes the job of teachers and how they must modify their tactics to successfully combine digital and conventional approaches. This study assesses the effects of digital technology on students' artistic expression, skill development, and interaction with conventional media through case studies and surveys. Additionally, it talks about how digital learning affects artistic creativity and craftsmanship on a psychological and cognitive level. The study emphasizes the necessity of a hybrid approach that preserves the fundamental tactile and experience elements of conventional art instruction while utilizing digital innovations. In the conclusion, the study offers suggestions for incorporating digital technologies in a way that enhances conventional teaching strategies rather than takes their place. It recommends a well-rounded curriculum that encourages both digital competence and conventional method mastery, guaranteeing that art students acquire a broad range of skills appropriate for modern artistic endeavors.